Preparation method and application of bismuth sulfide-reduced graphene oxide composite material

By growing rod-shaped Bi2S3 in situ on graphene oxide nanosheets, forming bismuth sulfide-reduced graphene oxide composite material, the problems of poor conductivity and low structural stability of bismuth sulfide materials are solved, and efficient electromagnetic wave absorption performance and simple process are achieved Process, suitable for large-scale production.

CN119277741AActive Publication Date: 2025-01-07UNIV OF ELECTRONICS SCI & TECH OF CHINA
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411382933.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The existing bismuth sulfide materials have poor electrical conductivity, low stability of a single rod-shaped structure, complex process and high cost, which limits their application in the field of electromagnetic wave absorption, and are difficult to meet the needs in complex environments.

Method used

Rod-shaped Bi2S3 was grown in situ on graphene oxide nanosheets by solvothermal method to form a bismuth sulfide-reduced graphene oxide composite material. By controlling the reaction parameters, it can adjust its conductivity and structure to achieve efficient electromagnetic wave absorption.

Benefits of technology

The bismuth sulfide-reduced graphene oxide composite material with adjustable conductivity, stable properties and broadband microwave absorption performance is achieved, which simplifies the process flow, reduces production costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119277741A_ABST
    Figure CN119277741A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electromagnetic wave absorbing materials, and provides a preparation method and application of a bismuth sulfide-reduced graphene oxide composite material. The invention aims to solve the problems of high cost, environmental pollution and insufficient absorption capacity of a single material of a traditional metal material absorbent. According to the main scheme, the preparation method comprises the following steps: synthesizing a graphene oxide nanosheet, taking ethylene glycol as a solvent medium, taking polyvinylpyrrolidone K30 as a surfactant, adding bismuth nitrate pentahydrate and thiourea, and performing solvothermal reaction to prepare the bismuth sulfide-reduced graphene oxide composite material in situ. The electromagnetic functional material comprises a microwave absorbing material and an electromagnetic shielding material, and the composite material is used as a filling agent and is mixed with paraffin or epoxy resin to be coated on the surface of a protected object, so that electromagnetic wave absorption and shielding are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electromagnetic wave absorbing materials and provides a preparation method and application of a bismuth sulfide-reduced graphene oxide composite material. Background Art

[0002] In recent years, the widespread use of electromagnetic waves has brought about serious problems such as mutual interference between electronic devices and human health. Therefore, the development of materials that effectively absorb electromagnetic waves has become a key issue that needs to be solved urgently. Although traditional metal material absorbers have excellent performance, their high cost and prominent environmental pollution problems restrict their further application. In addition, the electromagnetic wave interference scenarios are complex, and the absorption capacity of a single material is not enough to meet the needs. It is urgent to develop new composite material absorbers.

[0003] Metal sulfide semiconductor materials have shown broad application prospects in the fields of catalysis, energy, optoelectronic devices, etc. due to their unique structure and properties, and have gradually become the focus of attention in the field of electromagnetic wave absorbers. Among them, bismuth sulfide is considered to have potential application value in wave absorption due to its excellent semiconductor properties and strong one-dimensional growth tendency.

[0004] However, the low electrical conductivity of bismuth sulfide limits its application. It usually needs to be compounded with other materials to improve its dielectric loss performance and achieve better wave absorption effect. It is usually compounded with carbon materials. Researchers have adopted a variety of strategies to prepare such absorbers, such as introducing matching units, introducing magnetic units, enhancing polarization relaxation, and designing super-composite materials. Huang Xiaoxiao's research group at Harbin Institute of Technology prepared a micron flower-shaped 1T / 2H phase molybdenum disulfide absorbing material. The study found that when the matching thickness of the material was 2.68mm, the reflection loss was as low as nearly -59.8dB, and when the matching thickness was 2.48mm, the effective absorption bandwidth was 6.8GHz. (Huang Xiaoxiao, Yan Yuefeng, Zhang Kaili, Qin Guangyu, Zhou Yu. Preparation method of micron flower-shaped 1T / 2H phase molybdenum disulfide absorbing material CN117963987A, 2024-05-03.) Jiang et al. prepared boron nitride / reduced graphene oxide (BN / RGO) nanocomposite materials by a one-step thermal nitridation process. The absorbing performance of the obtained nano BN / RGO hybrid material was 4.2 GHz with an effective absorption bandwidth of 4.2 GHz at a thickness of 2.6 mm, achieving a maximum reflection loss (RL) of -48.9 dB. (Zhiyang Jiang, Haoxu Si, Xin Chen, Huimin Liu, Lei Zhang, Yahong Zhang, Chunhong Gong, and Jingwei Zhang, Composites Communications 22, 100503 (2020).) In summary, bismuth sulfide materials have good potential for electromagnetic wave absorption performance, but there are usually several outstanding problems: First, pure bismuth sulfide has poor conductivity and easy impedance mismatch, which makes its absorption performance poor; Second, the single rod-shaped structure has low stability, and the complex absorption environment requires a more stable architecture; Third, the process is complicated and the cost is relatively high, which is not conducive to large-scale production. Summary of the invention

[0005] The present invention aims to provide a bismuth sulfide-reduced graphene oxide composite material which is easy to prepare, has tunable conductivity, stable properties, and has strong broadband microwave absorption performance, and a preparation method thereof. Another object is to provide the application of the bismuth sulfide-reduced graphene oxide composite material in electromagnetic wave absorption.

[0006] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0007] The invention provides a bismuth sulfide-reduced graphene oxide composite material. The surface of the reduced graphene oxide nanosheet has rod-shaped Bi2S3, and the rod-shaped Bi2S3 is in-situ grown in a solvothermal process of the graphene oxide nanosheet.

[0008] The present invention also provides a method for preparing a bismuth sulfide-reduced graphene oxide composite material, comprising the following steps:

[0009] Synthesize graphene oxide nanosheets for later use;

[0010] Using ethylene glycol as a solvent medium, polyvinyl pyrrolidone K30 as a surfactant, and graphene oxide nanosheets as a substrate, bismuth nitrate pentahydrate and thiourea are added, mixed and stirred evenly, and then transferred to the inner lining of a hydrothermal autoclave, and heated to a reaction temperature between 180 and 220°C;

[0011] The solvent thermal reaction time is 8 to 18 hours. After the reaction is completed, the hydrothermal kettle is completely cooled to room temperature. The black powder formed on the inner wall of the lining is the bismuth sulfide-reduced graphene oxide composite material.

[0012] In the above scheme, the polytetrafluoroethylene lining of the hydrothermal reactor is cleaned:

[0013] Rinse the inner wall of the polytetrafluoroethylene liner and the inner wall of the lid of the hydrothermal kettle with running tap water, then rinse the inner wall of the inner village and the inner wall of the lid with 800-1200 mL of deionized water, then fill the liner with 50-100 mL of anhydrous ethanol, place it in an ultrasonic cleaner, and ultrasonically clean it for 15-25 minutes;

[0014] In the above scheme, the synthesis of graphene oxide powder is:

[0015] Step a1. Place a dry container in a water bath, fix a mechanical stirring device above the bottle mouth, add 3g of phosphorus flake graphite, 360mL of sulfuric acid, 40mL of orthophosphoric acid and 18g of potassium permanganate in sequence, and stir in a water bath at 46°C for 12 to 16h;

[0016] Step a2. Place a beaker containing 350-450 mL of deionized water in an ice bath, slowly add the stirred solution in a1, and after cooling, add 10-15 mL of hydrogen peroxide dropwise until the solution turns bright yellow;

[0017] Step a3. The bright yellow solution described in step ② is then washed with deionized water for 3 to 5 times, centrifuged until the pH value of the solution is close to 7.0, and the final washed product is freeze-dried to obtain a dry graphene oxide powder, which is stored for later use;

[0018] In the above scheme, the synthesis of bismuth sulfide-reduced graphene oxide composite material:

[0019] Step b1. Dissolve 20 to 80 mg of the graphene oxide powder prepared in step a3 in 30 to 50 mL of ethylene glycol, ultrasonicate for 15 to 25 min, then add 0.05 to 0.2 g of polyvinyl pyrrolidone K30 powder and stir for 20 to 40 min;

[0020] Step b2. Add 0.8 to 1.5 g of bismuth nitrate pentahydrate and 0.1 to 0.6 g of thiourea, and then stir the mixed solution for 20 to 40 min;

[0021] Step b3 was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, sealed and maintained at 180 to 220 ° C for 8 to 18 hours;

[0022] Step b4. After the hydrothermal autoclave is completely cooled to room temperature, the polytetrafluoroethylene liner is opened and the black powder in the centrifuge tube is collected. The black powder is the bismuth sulfide-reduced graphene oxide composite material;

[0023] Step b5. Wash the black powder in step b4 with deionized water and anhydrous ethanol for multiple times, dry the black powder at 60-80°C, and store it for later use after it is completely dried.

[0024] The present invention also provides an application of a bismuth sulfide-reduced graphene oxide composite material. The bismuth sulfide-reduced graphene oxide composite material is used as an electromagnetic functional material, including a microwave absorbing material and an electromagnetic shielding material.

[0025] In the above scheme, the method of using the bismuth sulfide-reduced graphene oxide composite material is: the bismuth sulfide-reduced graphene oxide composite material is used as a filler, uniformly mixed with paraffin or epoxy resin in proportion, and coated on the surface of the protected object to use as a coating.

[0026] Because the present invention adopts the above technical means, it has the following beneficial effects:

[0027] (1) The bismuth sulfide-reduced graphene oxide composite material of the present invention has good electromagnetic wave absorption performance and can be used as an electromagnetic functional material, including but not limited to microwave absorption material and electromagnetic shielding material.

[0028] (2) The bismuth sulfide-reduced graphene oxide composite material is prepared in situ under solvent thermal conditions with graphene oxide nanosheets as the substrate, bismuth nitrate pentahydrate as the bismuth source, and thiourea as the sulfur source. It has the characteristics of simple reaction process flow, high yield, and tunable product conductivity.

[0029] (3) The morphology, performance and yield of the bismuth sulfide-reduced graphene oxide composite material can be adjusted by controlling the concentration of graphene oxide, the concentration of the sulfur source and the bismuth source, the temperature of the solvent thermal reaction and the reaction time. Therefore, the present invention has the characteristics of simple process, easy operation and scalable production. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM photo of the bismuth sulfide-reduced graphene oxide composite material obtained in Example 1 of the present invention;

[0031] Figure 2 This is a TEM photo of the bismuth sulfide-reduced graphene oxide composite material obtained in Example 1 of the present invention;

[0032] Figure 3 The XRD spectrum of the bismuth sulfide-reduced graphene oxide composite material obtained in Example 1 of the present invention;

[0033] Figure 4 This is a reflection loss spectrum of the bismuth sulfide-reduced graphene oxide composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION

[0034] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.

[0035] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.

[0036] The invention provides a bismuth sulfide-reduced graphene oxide composite material. The surface of the reduced graphene oxide nanosheet has rod-shaped Bi2S3, and the rod-shaped Bi2S3 is in-situ grown in a solvothermal process of the graphene oxide nanosheet.

[0037] The present invention also provides a method for preparing a bismuth sulfide-reduced graphene oxide composite material, comprising the following steps:

[0038] Synthesize graphene oxide nanosheets for later use;

[0039] Using ethylene glycol as a solvent medium, polyvinyl pyrrolidone K30 as a surfactant, and graphene oxide nanosheets as a substrate, bismuth nitrate pentahydrate and thiourea are added, mixed and stirred evenly, and then transferred to the inner lining of a hydrothermal autoclave, and heated to a reaction temperature between 180 and 220°C;

[0040] The solvent thermal reaction time is 8 to 18 hours. After the reaction is completed, the hydrothermal kettle is completely cooled to room temperature. The black powder formed on the inner wall of the lining is the bismuth sulfide-reduced graphene oxide composite material.

[0041] In the above scheme, the polytetrafluoroethylene lining of the hydrothermal reactor is cleaned:

[0042] Rinse the inner wall of the polytetrafluoroethylene liner and the inner wall of the lid of the hydrothermal kettle with running tap water, then rinse the inner wall of the inner village and the inner wall of the lid with 800-1200 mL of deionized water, then fill the liner with 50-100 mL of anhydrous ethanol, place it in an ultrasonic cleaner, and ultrasonically clean it for 15-25 minutes;

[0043] In the above scheme, the chemical reaction raw materials are prepared as follows:

[0044] The chemical raw materials required for preparing the bismuth sulfide-reduced graphene oxide composite material are prepared. All chemical reagents are analytical grade reagents and can be used directly without further purification, as follows:

[0045] Flake graphite: solid, purity ≥99.5%;

[0046] Potassium permanganate: solid, purity ≥99.5%;

[0047] Bismuth nitrate pentahydrate: solid, purity ≥99.0%;

[0048] Thiourea: solid, purity ≥99.0%;

[0049] Polyvinylpyrrolidone K30: solid, purity ≥99.0%;

[0050] Sulfuric acid: liquid, concentration ≥98%;

[0051] Orthophosphoric acid: liquid, purity ≥98%;

[0052] Hydrogen peroxide: liquid, concentration ≥ 30%;

[0053] Ethanol: liquid, purity ≥99.7%;

[0054] Ethylene glycol: liquid, purity ≥99.5%;

[0055] Deionized water: liquid, purity ≥99.99%.

[0056] In the above scheme, the synthesis of graphene oxide powder is:

[0057] Step a1. Place a dry container in a water bath, fix a mechanical stirring device above the bottle mouth, add 3g of phosphorus flake graphite, 360mL of sulfuric acid, 40mL of orthophosphoric acid and 18g of potassium permanganate in sequence, and stir in a water bath at 46°C for 12 to 16h;

[0058] Step a2. Place a beaker containing 350-450 mL of deionized water in an ice bath, slowly add the stirred solution in a1, and after cooling, add 10-15 mL of hydrogen peroxide dropwise until the solution turns bright yellow;

[0059] Step a3. The bright yellow solution described in step ② is then washed with deionized water for 3 to 5 times, centrifuged until the pH value of the solution is close to 7.0, and the final washed product is freeze-dried to obtain a dry graphene oxide powder, which is stored for later use;

[0060] In the above scheme, the synthesis of bismuth sulfide-reduced graphene oxide composite material:

[0061] Step b1. Dissolve 20 to 80 mg of the graphene oxide powder prepared in step a3 in 30 to 50 mL of ethylene glycol, ultrasonicate for 15 to 25 min, then add 0.05 to 0.2 g of polyvinyl pyrrolidone K30 powder and stir for 20 to 40 min;

[0062] Step b2. Add 0.8 to 1.5 g of bismuth nitrate pentahydrate and 0.1 to 0.6 g of thiourea, and then stir the mixed solution for 20 to 40 min;

[0063] Step b3 was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, sealed and maintained at 180 to 220 ° C for 8 to 18 hours;

[0064] Step b4. After the hydrothermal autoclave is completely cooled to room temperature, the polytetrafluoroethylene liner is opened and the black powder in the centrifuge tube is collected. The black powder is the bismuth sulfide-reduced graphene oxide composite material;

[0065] Step b5. Wash the black powder in step b4 with deionized water and anhydrous ethanol for multiple times, dry the black powder at 60-80°C, and store it for later use after it is completely dried.

[0066] The prepared black solid powder, i.e., bismuth sulfide-reduced graphene oxide composite material, was subjected to morphological, chemical composition, performance analysis and other characterizations. The composite material was subjected to morphological analysis using a field emission scanning electron microscope. The microstructure of the composite material was analyzed using a high-resolution transmission electron microscope. The composition of the product was analyzed using X-ray powder diffraction. The electromagnetic parameters of the composite material were tested using a vector network analyzer.

[0067] Conclusion: The product is black, a bismuth sulfide-reduced graphene oxide composite material; the rod-like structure has a diameter of 50 nanometers and a length of several microns; the sheet-like structure has an area of ​​tens of square microns; the product contains elements such as sulfur, bismuth, and carbon; the maximum reflection attenuation in the Ku band can reach 24.1 dB, and the effective absorption bandwidth can reach 6.72 GHz, which means it has good electromagnetic wave absorption performance.

[0068] The present invention also provides an application of a bismuth sulfide-reduced graphene oxide composite material. The bismuth sulfide-reduced graphene oxide composite material is used as an electromagnetic functional material, including a microwave absorbing material and an electromagnetic shielding material.

[0069] In the above scheme, the method of using the bismuth sulfide-reduced graphene oxide composite material is: the bismuth sulfide-reduced graphene oxide composite material is used as a filler, uniformly mixed with paraffin or epoxy resin in proportion, and coated on the surface of the protected object to use as a coating.

[0070] Embodiment 1:

[0071] The preparation method of the bismuth sulfide-reduced graphene oxide composite material of the present invention comprises the following steps:

[0072] (1) Synthesis of graphene oxide nanosheets.

[0073] Place a dry three-necked flask in a water bath, fix a mechanical stirring device above the flask mouth, add 3g of phosphorus flake graphite, 360mL of sulfuric acid, 40mL of orthophosphoric acid and 18g of potassium permanganate in sequence, and stir in a 46°C water bath for 12h:

[0074] Place a beaker containing 400 mL of deionized water in an ice bath, slowly add the solution stirred for 12 hours, and add 10 mL of hydrogen peroxide dropwise after cooling until the solution turns bright yellow. Then wash the bright yellow solution three times with deionized water, centrifuge until the pH value of the solution is close to 7.0, freeze-dry the final washed product to obtain dry graphene oxide powder, and store it for later use;

[0075] (2) Synthesis of bismuth sulfide-reduced graphene oxide composites

[0076] 20 mg of graphene oxide powder was dissolved in 40 mL of ethylene glycol, ultrasonicated for 15 min, and then 0.1 g of polyvinyl pyrrolidone K30 powder was added and stirred for 20 min. Subsequently, 1 g of bismuth nitrate pentahydrate and 0.2 g of thiourea were added, and the mixed solution was stirred for 20 min. The solution was then transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, sealed and kept at 180 ° C for 10 hours.

[0077] After the hydrothermal autoclave is completely cooled to room temperature, the polytetrafluoroethylene liner is carefully opened to collect the black powder in the centrifuge tube. The black powder is the bismuth sulfide-reduced graphene oxide composite material.

Claims

1. A bismuth sulfide-reduced graphene oxide composite material, characterized in that: The surface of reduced graphene oxide nanosheets has rod-shaped Bi2S3, which is in situ grown during the solvothermal process of graphene oxide nanosheets.

2. A method for preparing a bismuth sulfide-reduced graphene oxide composite material as claimed in claim 1, characterized in that: The following steps are involved: Synthesize graphene oxide nanosheets for later use; Using ethylene glycol as a solvent medium, polyvinyl pyrrolidone K30 as a surfactant, and graphene oxide nanosheets as a substrate, bismuth nitrate pentahydrate and thiourea are added, mixed and stirred evenly, and then transferred to the inner lining of a hydrothermal autoclave, and heated to a reaction temperature between 180 and 220°C; The solvent thermal reaction time is 8 to 18 hours. After the reaction is completed, the hydrothermal kettle is completely cooled to room temperature. The black powder formed on the inner wall of the lining is the bismuth sulfide-reduced graphene oxide composite material.

3. A method for preparing a bismuth sulfide-reduced graphene oxide composite material as claimed in claim 2, characterized in that: Cleaning of polytetrafluoroethylene lining of hydrothermal reactor: Rinse the inner wall of the polytetrafluoroethylene liner and the inner wall of the lid of the hydrothermal autoclave with running tap water, then rinse the inner wall of the inner village and the inner wall of the lid with 800-1200 mL of deionized water, then fill the liner with 50-100 mL of anhydrous ethanol, place it in an ultrasonic cleaner, and ultrasonically clean it for 15-25 minutes.

4. A method for preparing a bismuth sulfide-reduced graphene oxide composite material as claimed in claim 3, characterized in that: Synthesis of graphene oxide powder: Step a1. Place a dry container in a water bath, fix a mechanical stirring device above the bottle mouth, add 3g of phosphorus flake graphite, 360mL of sulfuric acid, 40mL of orthophosphoric acid and 18g of potassium permanganate in sequence, and stir in a water bath at 46°C for 12 to 16h; Step a2. Place a beaker containing 350-450 mL of deionized water in an ice bath, slowly add the stirred solution in a1, and after cooling, add 10-15 mL of hydrogen peroxide dropwise until the solution turns bright yellow; Step a3. The bright yellow solution described in ② is then washed with deionized water for 3 to 5 times, centrifuged until the pH value of the solution is close to 7.0, and the final washed product is freeze-dried to obtain dry graphene oxide powder, which is stored for later use.

5. A method for preparing a bismuth sulfide-reduced graphene oxide composite material as claimed in claim 4, characterized in that: Synthesis of Bismuth Sulfide-Reduced Graphene Oxide Composites: Step b1. Dissolve 20 to 80 mg of the graphene oxide powder prepared in step a3 in 30 to 50 mL of ethylene glycol, ultrasonicate for 15 to 25 min, then add 0.05 to 0.2 g of polyvinyl pyrrolidone K30 powder and stir for 20 to 40 min; Step b2. Add 0.8 to 1.5 g of bismuth nitrate pentahydrate and 0.1 to 0.6 g of thiourea, and then stir the mixed solution for 20 to 40 min; Step b3 was transferred to a 100 mL polytetrafluoroethylene-lined stainless steel autoclave, sealed and maintained at 180 to 220 ° C for 8 to 18 hours; Step b4. After the hydrothermal autoclave is completely cooled to room temperature, the polytetrafluoroethylene liner is opened to collect the black powder in the centrifuge tube, which is the bismuth sulfide-reduced graphene oxide composite material; Step b5. Wash the black powder in step b4 with deionized water and anhydrous ethanol for multiple times, dry the black powder at 60-80°C, and store it for later use after it is completely dried.

6. The use of a bismuth sulfide-reduced graphene oxide composite material as claimed in claim 1, characterized in that: The bismuth sulfide-reduced graphene oxide composite material is used as an electromagnetic functional material, including a microwave absorbing material and an electromagnetic shielding material.

7. The use of a bismuth sulfide-reduced graphene oxide composite material as claimed in claim 6, characterized in that: The method of using the bismuth sulfide-reduced graphene oxide composite material is as follows: the bismuth sulfide-reduced graphene oxide composite material is used as a filler, uniformly mixed with paraffin or epoxy resin in proportion, and coated on the surface of the protected object to use as a coating.

Citation Information

Patent Citations

  • Chemical preparation method of graphene-bismuth sulfide nanocomposite material

    CN102910617A

  • Preparation method of grapheme and ferriferrous oxide composite nanometer material

    CN103274396A

  • Preparation method of reduced graphene oxide / manganese ferrite nano-composite wave absorbing material

    CN108559445A

  • Preparation method of rodlike bismuth sulfide / reduced graphene oxide composite material

    CN113087016A

  • Hollow ferroferric oxide / reduced graphene oxide nano composite wave-absorbing material and preparation method thereof

    CN113395888A